High-gloss and high-covering ink for glass white board and preparation method of high-gloss and high-covering ink
By using a combination of composite diatomaceous earth and amphiphilic block copolymer, the gloss and covering effect of ink for glass white plates are improved, and the problem of layering and precipitation of inks for a long time is solved, and the ink effect with high stability and high erasability is achieved.
Patent Information
- Application Number
- CN202510058155.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-25
AI Technical Summary
If the ink is used for a long time, it is easy to produce layering and precipitation, and the gloss and covering effects are poor, which affects the application.
The stability and gloss of ink are improved by combining modified diatomaceous earth and amphiphilic block copolymers using a high gloss, high-covered ink formulation including pigments, composite diatomaceous earth, dispersants, resins, wetting agents and deionized water.
The high gloss and high hiding effect of ink is achieved, the stability and erasability of ink are improved, and the layering and precipitation problems are solved.
Smart Images

Figure BDA0005242036790000141 
Figure BDA0005242036790000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass whiteboard ink, in particular to a high-gloss and high-hiding ink for a glass whiteboard and a preparation method thereof. Background Art
[0002] Glass whiteboard is a new type of writing board with a smooth, transparent or translucent surface and high safety. It can clearly display written or drawn content and is often used as a tool in meetings, education or creative workspaces. The original intention of the glass whiteboard was to use specific whiteboard pens for writing. These handwritings can be easily erased without leaving marks or damaging the surface of the whiteboard. In order to avoid long-term contact between whiteboard pens and the human body, which may have an adverse effect on teachers' health, the use of glass whiteboard ink instead of traditional whiteboard pens can solve this problem.
[0003] Ink is injected into the matching writing pen and written on the glass whiteboard. It can replace chalk for teaching blackboard writing and office notes, which improves the dust pollution and improves the teaching environment. The injected ink is water-based ink, which has the advantages of dust-free and easy to erase. However, the ink is prone to stratification and precipitation after being left for a long time, and the writing is difficult to erase after a long time. The inorganic pigments in the ink are poorly dispersed, resulting in poor gloss of the ink. In addition, the ink has a low covering rate, which affects the application of the ink in the writing field. Summary of the invention
[0004] The invention provides a high-gloss and high-hiding ink for glass whiteboards and a preparation method thereof, which solves the problems that the ink is prone to precipitation after being left for a long time and the poor dispersibility of inorganic pigments leads to reduced gloss and hiding effect of the ink.
[0005] The technical solution of the present invention:
[0006] A high gloss, high hiding ink for glass whiteboards, comprising the following raw materials in parts by weight: 30-35 parts of pigment, 2-5 parts of composite diatomaceous earth, 8-10 parts of dispersant, 3-7 parts of resin, 0.2-0.5 parts of wetting agent, 50-60 parts of deionized water, and 5-8 parts of propylene glycol;
[0007] The composite diatomaceous earth is obtained by mixing and reacting modified diatomaceous earth, an amphiphilic block copolymer and hydroxypropyl methylcellulose;
[0008] The modified diatomaceous earth is obtained by mixing diatomaceous earth and n-butyl titanate, and then mixing with pretreated graphene oxide;
[0009] The amphiphilic block copolymer is obtained by mixed reaction of (2-hydroxyethyl) benzyl trithiocarbonate, ε-caprolactone and acrylic acid.
[0010] A method for preparing high-gloss and high-hiding ink for glass whiteboards comprises the following preparation steps:
[0011] S1. The pigment, deionized water and propylene glycol were mixed, stirred at a rate of 500-600r / min for 5-10min, composite diatomaceous earth, dispersant, resin and wetting agent were added, and stirred at a rate of 1800-2000r / min for 30-40min to obtain a mixture;
[0012] S2. Grind the mixture at a rotation speed of 1600-1800 rpm for 6-10 hours to obtain a high gloss, high hiding ink.
[0013] Furthermore, the pigment is selected from titanium dioxide or carbon black.
[0014] Furthermore, the dispersant is selected from any one of BKY-JET9142 dispersant, BKY-JET9132 dispersant, and EFKA-PX4701 dispersant.
[0015] Furthermore, the resin is selected from polyvinyl alcohol resin or acrylic resin.
[0016] Furthermore, the wetting agent is selected from polyoxyethylene alkylphenol ether or polyoxyethylene fatty alcohol ether.
[0017] Furthermore, the composite diatomite is specifically prepared by the following steps:
[0018] A1. Add n-butyl titanate and hydrofluoric acid to deionized water, stir evenly, add diatomaceous earth, stir at 500-600r / min for 30-40min, place in a reactor, react at 170-190°C for 8-10h, cool to room temperature, filter, wash, and dry to obtain diatomaceous earth loaded with nano-titanium dioxide;
[0019] A2. Add graphene oxide to Tris-HCl buffer at pH 8.5, stir evenly, add dopamine, stir and react for 4-5h, filter, wash and dry to obtain polydopamine-modified graphene oxide;
[0020] A3. The polydopamine-modified graphene oxide and the diatomaceous earth loaded with nano-titanium dioxide were added to deionized water, stirred at 1000-1200 r / min for 30-40 min, allowed to stand, filtered, washed, and dried to obtain modified diatomaceous earth;
[0021] A4. ε-caprolactone and (2-hydroxyethyl) benzyl trithiocarbonate were added to toluene, stirred evenly, reacted at 30-40°C for 5-6h, placed in hexane to form a precipitate, collected by filtration, and dried to obtain a complex;
[0022] A5. Add the complex, acrylic acid and azobisisobutyronitrile to N,N-dimethylformamide, stir evenly, react at 75-85°C for 5-6h, add chloroform, continue stirring for 10-20min, place in hexane for precipitation, collect the precipitate by filtration, wash and dry the precipitate to obtain an amphiphilic block copolymer;
[0023] A6. Add the amphiphilic block copolymer and hydroxypropyl methylcellulose to deionized water, stir evenly, add modified diatomaceous earth, stir at 60-70° C. for 1-2 hours, cool to room temperature, filter, wash, and dry to obtain composite diatomaceous earth.
[0024] Furthermore, in the above-mentioned A1 reaction process, n-butyl titanate is mixed with deionized water to form a hydrolyzate. Diatomaceous earth has a large specific area and a porous structure, and can adsorb the hydrolyzate into the pores of the diatomaceous earth. After a hydrothermal reaction at 170-190°C, n-butyl titanate is hydrolyzed and condensed to form titanium dioxide crystals. As the reaction proceeds, the titanium dioxide crystals grow and aggregate, thereby synthesizing nano-sized nano-titanium dioxide in the pores of the diatomaceous earth, forming diatomaceous earth loaded with nano-titanium dioxide.
[0025] Furthermore, during the above reaction A2, in the Tris-HCl buffer, dopamine can self-polymerize on the surface of graphene oxide to form polydopamine, thereby forming polydopamine-modified graphene oxide, so that the graphene oxide carries a large number of phenolic hydroxyl groups, which is beneficial for the graphene oxide to adhere to the surface of diatomaceous earth loaded with nano-titanium dioxide.
[0026] Furthermore, in the above-mentioned A3 reaction process, the polydopamine-modified graphene oxide has excellent adhesion and contains a large number of phenolic hydroxyl groups, which can adhere to the surface of diatomaceous earth loaded with nano-titanium dioxide to form modified diatomaceous earth.
[0027] Furthermore, in the above reaction process A4, in toluene solvent, (2-hydroxyethyl)benzyl trithiocarbonate is used as a ring-opening polymerization initiator, so that (2-hydroxyethyl)benzyl trithiocarbonate can undergo a ring-opening polymerization reaction with ε-caprolactone to form a complex.
[0028] Furthermore, in the above-mentioned reaction process A5, in N,N-dimethylformamide, diisobutyronitrile is used as a free radical initiator, and (2-hydroxyethyl) benzyl trithiocarbonate in the complex is used as a reversible addition-fragmentation chain transfer agent, so that the complex can copolymerize with acrylic acid to form an amphiphilic block copolymer.
[0029] Furthermore, during the above-mentioned A6 reaction process, the hydrophobic segments of the amphiphilic block copolymer can interact with the modified diatomaceous earth, so that the amphiphilic block copolymer is wrapped on the surface of the modified diatomaceous earth, and the hydroxypropyl methylcellulose has good fluidity and can be dispersed in the amphiphilic block copolymer and wrapped on the surface of the modified diatomaceous earth to form a composite diatomaceous earth.
[0030] Furthermore, in step A1, the ratio of n-butyl titanate, hydrofluoric acid, deionized water and diatomaceous earth is (4-6) mL: (1-1.4) mL: (45-55) mL: (10-11) g.
[0031] Furthermore, in step A2, the ratio of graphene oxide, Tris-HCl buffer and dopamine is (2-3) g: (45-55) mL: (0.4-0.6) g.
[0032] Furthermore, in step A3, the amount ratio of the polydopamine-modified graphene oxide, the diatomaceous earth loaded with nano-titanium dioxide and the deionized water is (1-2) g: (5-6) g: (25-35) mL.
[0033] Furthermore, in step A4, the ratio of the amount of ε-caprolactone, (2-hydroxyethyl) benzyl trithiocarbonate and toluene is (1-2) g: (0.4-0.6) g: (18-22) mL.
[0034] Furthermore, in step A5, the ratio of the amount of the complex, acrylic acid, azobisisobutyronitrile, N,N-dimethylformamide and chloroform is (1-3) g: (2-3) g: (0.03-0.07) g: (18-22) mL: (8-12) mL.
[0035] Furthermore, in step A6, the ratio of the amount of the amphiphilic block copolymer, hydroxypropyl methylcellulose, deionized water and modified diatomaceous earth is (5-6) g: (2-3) g: (45-55) mL: (8-12) g.
[0036] Furthermore, the particle size of graphene oxide is 0.1-1 μm.
[0037] Furthermore, the diatomaceous earth particle size is 1-2 μm.
[0038] The present invention has the following beneficial effects:
[0039] (1) In the technical scheme of the present invention, nano-sized nano-titanium dioxide is synthesized in the pores of diatomite. On the one hand, nano-sized nano-titanium dioxide is synthesized in the pores of diatomite, the pore size of diatomite is refined, and the porosity of diatomite is increased, which is beneficial for the porous structure of diatomite to adsorb pigments and binders in ink, play a role as a bridge, improve the stability of ink, and is beneficial to form high-gloss, high-hiding ink. On the other hand, diatomite serves as a carrier of nano-titanium dioxide to avoid agglomeration of nano-titanium dioxide. Nano-titanium dioxide has a high refractive index and light scattering properties, so that the ink fully reflects light under illumination, and has a good synergistic effect with diatomite in improving the gloss of ink.
[0040] (2) In the technical solution of the present invention, polydopamine is formed by self-polymerization on the surface of graphene oxide, so that the graphene oxide carries a large number of phenolic hydroxyl groups, and then the polydopamine-modified graphene oxide can be adhered to the surface of diatomaceous earth loaded with nano-titanium dioxide. On the one hand, graphene oxide has a high specific surface area and abundant reaction sites, and can interact with the ink raw materials to disperse the diatomaceous earth in the ink matrix, thereby improving the dispersibility of the diatomaceous earth in the ink. On the other hand, the lamellar structure of graphene oxide can form a dense physical barrier layer in the ink, thereby effectively covering the base color of the glass whiteboard, so that the ink presents a higher covering effect.
[0041] (3) In the technical scheme of the present invention, (2-hydroxyethyl) benzyl trithiocarbonate, ε-caprolactone and acrylic acid are mixed and reacted to form an amphiphilic block copolymer, and hydroxypropyl methylcellulose has good fluidity and can be dispersed in the amphiphilic block copolymer and wrapped together on the surface of the modified diatomaceous earth to form a composite diatomaceous earth. On the one hand, the hydrophilic chain segments of the amphiphilic block copolymer extend in the ink system, so that the composite diatomaceous earth is evenly dispersed in the ink matrix, enhancing the gloss and high hiding power of the ink, and the hydrophobic chains of the amphiphilic block copolymer in the composite diatomaceous earth can also interact with the lipophilic pigment, so that the pigment has excellent dispersibility, thereby improving the stability and high hiding rate of the ink. On the other hand, hydroxypropyl methylcellulose has good film-forming properties, so that the ink forms a continuous polymer film, so that the ink can be easily wiped off from the glass whiteboard. DETAILED DESCRIPTION
[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.
[0044] Among them, the pigment is carbon black, CAS: 1333-86-4, Shanghai Kaiyin Chemical Co., Ltd.
[0045] The dispersant is BKY-JET9142 dispersant, Dongguan Huazhiyuan Chemical Co., Ltd.
[0046] The resin is polyvinyl alcohol resin, from Guangzhou Julang Chemical Co., Ltd.
[0047] The wetting agent is polyoxyethylene alkylphenol ether, Jiangsu Xinlun Petrochemical Co., Ltd.
[0048] The particle size of graphene oxide is 0.5 μm, and the particle size of diatomaceous earth is 1.5 μm, Shanghai Aladdin Biochemical Technology Co., Ltd.
[0049] Example 1
[0050] A high gloss, high hiding ink for glass whiteboards, comprising the following raw materials in parts by weight: 30 parts of carbon black, 2 parts of composite diatomaceous earth, 8 parts of BKY-JET9142 dispersant, 3 parts of polyvinyl alcohol resin, 0.2 parts of polyoxyethylene alkylphenol ether, 50 parts of deionized water, and 5 parts of propylene glycol;
[0051] A method for preparing high-gloss and high-hiding ink for glass whiteboards comprises the following preparation steps:
[0052] S1. The carbon black, deionized water and propylene glycol were mixed and stirred at a rate of 500 r / min for 5 min, and composite diatomaceous earth, BKY-JET9142 dispersant, polyvinyl alcohol resin and polyoxyethylene alkylphenol ether were added and stirred at a rate of 1800 r / min for 30 min to obtain a mixture;
[0053] S2. The mixture was ground at a rotation speed of 1600 rpm for 6 h to obtain a high gloss, high hiding ink.
[0054] The composite diatomite is specifically prepared by the following steps:
[0055] A1. Add 4 mL of n-butyl titanate and 1 mL of hydrofluoric acid to 45 mL of deionized water, stir evenly, add 10 g of diatomaceous earth, stir at 500 r / min for 30 min, place in a reactor, react at 170 ° C for 8 h, cool to room temperature, filter, wash with deionized water 3 times, wash with ethanol 3 times, and dry in an oven at 70 ° C for 10 min to obtain diatomaceous earth loaded with nano-titanium dioxide;
[0056] A2. Add 2 g of graphene oxide to 45 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.4 g of dopamine, stir and react for 4 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified graphene oxide;
[0057] A3. 1 g of polydopamine-modified graphene oxide and 5 g of diatomaceous earth loaded with nano-titanium dioxide were added to 25 mL of deionized water, stirred at 1000 r / min for 30 min, allowed to stand for 1 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain modified diatomaceous earth;
[0058] A4. 1 g of ε-caprolactone and 0.4 g of (2-hydroxyethyl) benzyl trithiocarbonate were added to 18 mL of toluene, stirred evenly, reacted at 30°C for 5 h, placed in 50 mL of hexane to form a precipitate, collected by filtration, and dried in an oven at 60°C for 10 min to obtain a composite;
[0059] A5. 1 g of the complex, 2 g of acrylic acid and 0.03 g of azobisisobutyronitrile were added to 18 mL of N,N-dimethylformamide, stirred evenly, and reacted at 75°C for 5 h. 8 mL of chloroform was added and stirred for 10 min. The mixture was placed in 50 mL of hexane for precipitation. The precipitate was collected by filtration, washed with methanol 5 times, and dried in an oven at 60°C for 10 min to obtain an amphiphilic block copolymer.
[0060] A6. Add 5 g of amphiphilic block copolymer and 2 g of hydroxypropyl methylcellulose to 45 mL of deionized water, stir evenly, add 8 g of modified diatomaceous earth, stir at 60°C for 1 h, cool to room temperature, filter, wash with deionized water 3 times, and dry at 70°C for 10 min to obtain composite diatomaceous earth.
[0061] Example 2
[0062] A high gloss, high hiding ink for glass whiteboards, comprising the following raw materials in parts by weight: 33 parts of carbon black, 3 parts of composite diatomaceous earth, 9 parts of BKY-JET9142 dispersant, 5 parts of polyvinyl alcohol resin, 0.3 parts of polyoxyethylene alkylphenol ether, 55 parts of deionized water, and 7 parts of propylene glycol;
[0063] A method for preparing high-gloss and high-hiding ink for glass whiteboards comprises the following preparation steps:
[0064] S1. The carbon black, deionized water and propylene glycol were mixed and stirred at a rate of 550 r / min for 8 min, and composite diatomaceous earth, BKY-JET9142 dispersant, polyvinyl alcohol resin and polyoxyethylene alkylphenol ether were added and stirred at a rate of 1900 r / min for 35 min to obtain a mixture;
[0065] S2. The mixture was ground at a rotation speed of 1700 rpm for 8 h to obtain a high gloss, high hiding ink.
[0066] The composite diatomite is specifically prepared by the following steps:
[0067] A1. Add 5 mL of n-butyl titanate and 1.2 mL of hydrofluoric acid to 50 mL of deionized water, stir evenly, add 10.5 g of diatomaceous earth, stir at 550 r / min for 35 min, place in a reactor, react at 180 ° C for 9 h, cool to room temperature, filter, wash with deionized water 3 times, wash with ethanol 3 times, and dry in an oven at 70 ° C for 10 min to obtain diatomaceous earth loaded with nano-titanium dioxide;
[0068] A2. Add 2.5 g of graphene oxide to 50 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.5 g of dopamine, stir and react for 4.5 h, filter, wash with deionized water three times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified graphene oxide;
[0069] A3. 1.5 g of polydopamine-modified graphene oxide and 5.5 g of diatomaceous earth loaded with nano-titanium dioxide were added to 30 mL of deionized water, stirred at 1100 r / min for 35 min, allowed to stand for 1 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain modified diatomaceous earth;
[0070] A4. 1.5 g of ε-caprolactone and 0.5 g of (2-hydroxyethyl) benzyl trithiocarbonate were added to 20 mL of toluene, stirred evenly, reacted at 35 ° C for 5.5 h, placed in 50 mL of hexane to form a precipitate, collected by filtration, and dried in an oven at 60 ° C for 10 min to obtain a composite;
[0071] A5. 2 g of the complex, 2.5 g of acrylic acid and 0.05 g of azobisisobutyronitrile were added to 20 mL of N,N-dimethylformamide, stirred evenly, and reacted at 80°C for 5.5 h. 10 mL of chloroform was added and stirred for 15 min. The mixture was placed in 50 mL of hexane for precipitation. The precipitate was collected by filtration, washed with methanol 5 times, and dried in an oven at 60°C for 10 min to obtain an amphiphilic block copolymer.
[0072] A6. Add 5.5 g of amphiphilic block copolymer and 2.5 g of hydroxypropyl methylcellulose to 50 mL of deionized water, stir evenly, add 10 g of modified diatomaceous earth, stir at 65 ° C for 1.5 h, cool to room temperature, filter, wash with deionized water 3 times, and dry at 70 ° C for 10 min to obtain composite diatomaceous earth.
[0073] Example 3
[0074] A high gloss, high hiding ink for glass whiteboards, comprising the following raw materials in parts by weight: 35 parts of carbon black, 5 parts of composite diatomaceous earth, 10 parts of BKY-JET9142 dispersant, 7 parts of polyvinyl alcohol resin, 0.5 parts of polyoxyethylene alkylphenol ether, 60 parts of deionized water, and 8 parts of propylene glycol;
[0075] A method for preparing high-gloss and high-hiding ink for glass whiteboards comprises the following preparation steps:
[0076] S1. The carbon black, deionized water and propylene glycol were mixed and stirred at a rate of 600 r / min for 10 min, and composite diatomaceous earth, BKY-JET9142 dispersant, polyvinyl alcohol resin and polyoxyethylene alkylphenol ether were added and stirred at a rate of 2000 r / min for 40 min to obtain a mixture;
[0077] S2. The mixture was ground at a rotation speed of 1800 rpm for 10 h to obtain a high gloss, high hiding ink.
[0078] The composite diatomite is specifically prepared by the following steps:
[0079] A1. Add 6 mL of n-butyl titanate and 1.4 mL of hydrofluoric acid to 55 mL of deionized water, stir evenly, add 11 g of diatomaceous earth, stir at 600 r / min for 40 min, place in a reactor, react at 190 ° C for 10 h, cool to room temperature, filter, wash with deionized water 3 times, wash with ethanol 3 times, and dry in an oven at 70 ° C for 10 min to obtain diatomaceous earth loaded with nano-titanium dioxide;
[0080] A2. Add 3 g of graphene oxide to 45 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.6 g of dopamine, stir and react for 5 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified graphene oxide;
[0081] A3. 2 g of polydopamine-modified graphene oxide and 6 g of diatomaceous earth loaded with nano-titanium dioxide were added to 35 mL of deionized water, stirred at 1200 r / min for 40 min, allowed to stand for 1 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain modified diatomaceous earth;
[0082] A4. 2 g of ε-caprolactone and 0.6 g of (2-hydroxyethyl) benzyl trithiocarbonate were added to 22 mL of toluene, stirred evenly, reacted at 40 ° C for 6 h, placed in 50 mL of hexane to form a precipitate, collected the precipitate by filtration, and dried in an oven at 60 ° C for 10 min to obtain a composite;
[0083] A5. 3 g of the complex, 3 g of acrylic acid and 0.07 g of azobisisobutyronitrile were added to 22 mL of N,N-dimethylformamide, stirred evenly, and reacted at 85°C for 6 h. 12 mL of chloroform was added and stirred for 20 min. The mixture was placed in 50 mL of hexane for precipitation. The precipitate was collected by filtration, washed with methanol 5 times, and dried in an oven at 60°C for 10 min to obtain an amphiphilic block copolymer.
[0084] A6. Add 6 g of amphiphilic block copolymer and 3 g of hydroxypropyl methylcellulose to 55 mL of deionized water, stir evenly, add 12 g of modified diatomaceous earth, stir at 70°C for 2 h, cool to room temperature, filter, wash with deionized water 3 times, and dry at 70°C for 10 min to obtain composite diatomaceous earth.
[0085] Comparative Example 1
[0086] A high gloss, high hiding ink for glass whiteboards, comprising the following raw materials in parts by weight: 35 parts of carbon black, 5 parts of composite diatomaceous earth, 10 parts of BKY-JET9142 dispersant, 7 parts of polyvinyl alcohol resin, 0.5 parts of polyoxyethylene alkylphenol ether, 60 parts of deionized water, and 8 parts of propylene glycol;
[0087] A method for preparing high-gloss and high-hiding ink for glass whiteboards comprises the following preparation steps:
[0088] S1. The carbon black, deionized water and propylene glycol were mixed and stirred at a rate of 600 r / min for 10 min, and composite diatomaceous earth, BKY-JET9142 dispersant, polyvinyl alcohol resin and polyoxyethylene alkylphenol ether were added and stirred at a rate of 2000 r / min for 40 min to obtain a mixture;
[0089] S2. The mixture was ground at a rotation speed of 1800 rpm for 10 h to obtain a high gloss, high hiding ink.
[0090] The composite diatomite is specifically prepared by the following steps:
[0091] A1. Add 3 g of graphene oxide to 45 mL of Tris-HCl buffer with a pH of 8.5, stir evenly, add 0.6 g of dopamine, stir and react for 5 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified graphene oxide;
[0092] A2. 2 g of polydopamine-modified graphene oxide and 6 g of diatomaceous earth were added to 35 mL of deionized water, stirred at 1200 r / min for 40 min, allowed to stand for 1 h, filtered, washed with deionized water 3 times, and dried in an oven at 70 ° C for 10 min to obtain modified diatomaceous earth;
[0093] A3. 2 g of ε-caprolactone and 0.6 g of (2-hydroxyethyl) benzyl trithiocarbonate were added to 22 mL of toluene, stirred evenly, reacted at 40 ° C for 6 h, placed in 50 mL of hexane to form a precipitate, collected by filtration, and dried in an oven at 60 ° C for 10 min to obtain a composite;
[0094] A4. 3 g of the complex, 3 g of acrylic acid and 0.07 g of azobisisobutyronitrile were added to 22 mL of N,N-dimethylformamide, stirred evenly, and reacted at 85°C for 6 h. 12 mL of chloroform was added and stirred for 20 min. The mixture was placed in 50 mL of hexane for precipitation. The precipitate was collected by filtration, washed with methanol 5 times, and dried in an oven at 60°C for 10 min to obtain an amphiphilic block copolymer.
[0095] A5. Add 6 g of amphiphilic block copolymer and 3 g of hydroxypropyl methylcellulose to 55 mL of deionized water, stir evenly, add 12 g of modified diatomaceous earth, stir at 70°C for 2 h, cool to room temperature, filter, wash with deionized water 3 times, and dry at 70°C for 10 min to obtain composite diatomaceous earth.
[0096] Comparative Example 2
[0097] A high gloss, high hiding ink for glass whiteboards, comprising the following raw materials in parts by weight: 35 parts of carbon black, 5 parts of composite diatomaceous earth, 10 parts of BKY-JET9142 dispersant, 7 parts of polyvinyl alcohol resin, 0.5 parts of polyoxyethylene alkylphenol ether, 60 parts of deionized water, and 8 parts of propylene glycol;
[0098] A method for preparing high-gloss and high-hiding ink for glass whiteboards comprises the following preparation steps:
[0099] S1. The carbon black, deionized water and propylene glycol were mixed and stirred at a rate of 600 r / min for 10 min, and composite diatomaceous earth, BKY-JET9142 dispersant, polyvinyl alcohol resin and polyoxyethylene alkylphenol ether were added and stirred at a rate of 2000 r / min for 40 min to obtain a mixture;
[0100] S2. The mixture was ground at a rotation speed of 1800 rpm for 10 h to obtain a high gloss, high hiding ink.
[0101] The composite diatomite is specifically prepared by the following steps:
[0102] A1. Add 6 mL of n-butyl titanate and 1.4 mL of hydrofluoric acid to 55 mL of deionized water, stir evenly, add 11 g of diatomaceous earth, stir at 600 r / min for 40 min, place in a reactor, react at 190 ° C for 10 h, cool to room temperature, filter, wash with deionized water 3 times, wash with ethanol 3 times, and dry in an oven at 70 ° C for 10 min to obtain diatomaceous earth loaded with nano-titanium dioxide;
[0103] A2. 2 g of graphene oxide and 6 g of diatomaceous earth loaded with nano-titanium dioxide were added to 35 mL of deionized water, stirred at 1200 r / min for 40 min, allowed to stand for 1 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain modified diatomaceous earth;
[0104] A3. 2 g of ε-caprolactone and 0.6 g of (2-hydroxyethyl) benzyl trithiocarbonate were added to 22 mL of toluene, stirred evenly, reacted at 40 ° C for 6 h, placed in 50 mL of hexane to form a precipitate, collected by filtration, and dried in an oven at 60 ° C for 10 min to obtain a composite;
[0105] A4. 3 g of the complex, 3 g of acrylic acid and 0.07 g of azobisisobutyronitrile were added to 22 mL of N,N-dimethylformamide, stirred evenly, and reacted at 85°C for 6 h. 12 mL of chloroform was added and stirred for 20 min. The mixture was placed in 50 mL of hexane for precipitation. The precipitate was collected by filtration, washed with methanol 5 times, and dried in an oven at 60°C for 10 min to obtain an amphiphilic block copolymer.
[0106] A5. Add 6 g of amphiphilic block copolymer and 3 g of hydroxypropyl methylcellulose to 55 mL of deionized water, stir evenly, add 12 g of modified diatomaceous earth, stir at 70°C for 2 h, cool to room temperature, filter, wash with deionized water 3 times, and dry at 70°C for 10 min to obtain composite diatomaceous earth.
[0107] Comparative Example 3
[0108] A high gloss, high hiding ink for glass whiteboards, comprising the following raw materials in parts by weight: 35 parts of carbon black, 5 parts of composite diatomaceous earth, 10 parts of BKY-JET9142 dispersant, 7 parts of polyvinyl alcohol resin, 0.5 parts of polyoxyethylene alkylphenol ether, 60 parts of deionized water, and 8 parts of propylene glycol;
[0109] A method for preparing high-gloss and high-hiding ink for glass whiteboards comprises the following preparation steps:
[0110] S1. The carbon black, deionized water and propylene glycol were mixed and stirred at a rate of 600 r / min for 10 min, and composite diatomaceous earth, BKY-JET9142 dispersant, polyvinyl alcohol resin and polyoxyethylene alkylphenol ether were added and stirred at a rate of 2000 r / min for 40 min to obtain a mixture;
[0111] S2. The mixture was ground at a rotation speed of 1800 rpm for 10 h to obtain a high gloss, high hiding ink.
[0112] The composite diatomite is specifically prepared by the following steps:
[0113] A1. Add 6 mL of n-butyl titanate and 1.4 mL of hydrofluoric acid to 55 mL of deionized water, stir evenly, add 11 g of diatomaceous earth, stir at 600 r / min for 40 min, place in a reactor, react at 190 ° C for 10 h, cool to room temperature, filter, wash with deionized water 3 times, wash with ethanol 3 times, and dry in an oven at 70 ° C for 10 min to obtain diatomaceous earth loaded with nano-titanium dioxide;
[0114] A2. Add 3 g of graphene oxide to 45 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.6 g of dopamine, stir and react for 5 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified graphene oxide;
[0115] A3. 2 g of polydopamine-modified graphene oxide and 6 g of diatomaceous earth loaded with nano-titanium dioxide were added to 35 mL of deionized water, stirred at 1200 r / min for 40 min, allowed to stand for 1 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain modified diatomaceous earth;
[0116] A4. Add 3 g of acrylic acid and 0.07 g of azobisisobutyronitrile to 22 mL of N,N-dimethylformamide, stir evenly, react at 85 ° C for 6 h, add 12 mL of chloroform and stir for 20 min, filter, wash with methanol 5 times, and dry in an oven at 60 ° C for 10 min to obtain a polyacrylic acid resin;
[0117] A5. Add 6 g of polyacrylic acid resin and 3 g of hydroxypropyl methylcellulose to 55 mL of deionized water, stir evenly, add 12 g of modified diatomaceous earth, stir at 70°C for 2 h, cool to room temperature, filter, wash with deionized water 3 times, and dry at 70°C for 10 min to obtain composite diatomaceous earth.
[0118] Comparative Example 4
[0119] A high gloss, high hiding ink for glass whiteboards, comprising the following raw materials in parts by weight: 35 parts of carbon black, 5 parts of composite diatomaceous earth, 10 parts of BKY-JET9142 dispersant, 7 parts of polyvinyl alcohol resin, 0.5 parts of polyoxyethylene alkylphenol ether, 60 parts of deionized water, and 8 parts of propylene glycol;
[0120] A method for preparing high-gloss and high-hiding ink for glass whiteboards comprises the following preparation steps:
[0121] S1. The carbon black, deionized water and propylene glycol were mixed and stirred at a rate of 600 r / min for 10 min, and composite diatomaceous earth, BKY-JET9142 dispersant, polyvinyl alcohol resin and polyoxyethylene alkylphenol ether were added and stirred at a rate of 2000 r / min for 40 min to obtain a mixture;
[0122] S2. The mixture was ground at a rotation speed of 1800 rpm for 10 h to obtain a high gloss, high hiding ink.
[0123] The composite diatomite is specifically prepared by the following steps:
[0124] A1. Add 6 mL of n-butyl titanate and 1.4 mL of hydrofluoric acid to 55 mL of deionized water, stir evenly, add 11 g of diatomaceous earth, stir at 600 r / min for 40 min, place in a reactor, react at 190 ° C for 10 h, cool to room temperature, filter, wash with deionized water 3 times, wash with ethanol 3 times, and dry in an oven at 70 ° C for 10 min to obtain diatomaceous earth loaded with nano-titanium dioxide;
[0125] A2. Add 3 g of graphene oxide to 45 mL of Tris-HCl buffer at pH 8.5, stir evenly, add 0.6 g of dopamine, stir and react for 5 h, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 min to obtain polydopamine-modified graphene oxide;
[0126] A3. 2 g of polydopamine-modified graphene oxide and 6 g of diatomaceous earth loaded with nano-titanium dioxide were added to 35 mL of deionized water, stirred at 1200 r / min for 40 min, allowed to stand for 1 h, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain modified diatomaceous earth;
[0127] A4. 2 g of ε-caprolactone and 0.6 g of (2-hydroxyethyl) benzyl trithiocarbonate were added to 22 mL of toluene, stirred evenly, reacted at 40 ° C for 6 h, placed in 50 mL of hexane to form a precipitate, collected the precipitate by filtration, and dried in an oven at 60 ° C for 10 min to obtain a composite;
[0128] A5. Add 3 g of the complex, 3 g of acrylic acid and 0.07 g of azobisisobutyronitrile to 22 mL of N,N-dimethylformamide, stir evenly, and react at 85°C for 6 h. Add 12 mL of chloroform and stir for 20 min. Place in 50 mL of hexane for precipitation. Collect the precipitate by filtration, wash the precipitate with methanol 5 times, and dry in an oven at 60°C for 10 min to obtain an amphiphilic block copolymer.
[0129] A6. Add 6 g of the amphiphilic block copolymer to 55 mL of deionized water, stir evenly, add 12 g of modified diatomaceous earth, stir at 70°C for 2 h, cool to room temperature, filter, wash with deionized water 3 times, and dry at 70°C for 10 min to obtain composite diatomaceous earth.
[0130] The performance of the high gloss and high hiding inks prepared in Examples 1-3 and Comparative Examples 1-4 is now tested.
[0131] Stability: Place the high gloss, high hiding ink prepared above at room temperature for 24 hours to observe whether the ink forms precipitation, and then write on a glass whiteboard to observe the writing effect;
[0132] Erasability: Use a damp cloth to wipe the writing on the glass whiteboard and observe the wiping effect;
[0133] Evaluation of hiding effect: The hiding effect of the high gloss, high hiding ink prepared above on a glass white board was observed.
[0134] Glossiness test: Use a gloss meter (instrument model: MN gloss meter) to test the glossiness of the ink at an incident angle of 60°, and record the glossiness G 60 ;
[0135] The test results are shown in Table 1 below.
[0136] Table 1 Performance test of high gloss and high hiding ink prepared in Examples 1-3 and Comparative Examples 1-4
[0137]
[0138]
[0139] It can be seen from the data in Table 1 that the high gloss and high hiding inks prepared in Examples 1-3 have high stability and erasability.
[0140] In Comparative Example 1, the diatomaceous earth loaded with nano-titanium dioxide was replaced with composite diatomaceous earth prepared by diatomaceous earth and added to the high-gloss, high-hiding ink, and its gloss and hiding power decreased, proving that the synthesis of nano-sized nano-titanium dioxide in the pores of diatomaceous earth increases the porosity of diatomaceous earth, plays a bridging role, improves the stability of the ink, and is conducive to the formation of high-gloss, high-hiding ink. In addition, nano-titanium dioxide has a high refractive index and light scattering properties, which can improve the gloss of the ink.
[0141] In Comparative Example 2, the composite diatomite prepared by replacing the polydopamine-modified graphene oxide with graphene oxide was added to the high-gloss, high-hiding ink, and its stability, gloss and hiding power decreased, proving that polydopamine was self-polymerized on the surface of graphene oxide, and then the polydopamine-modified graphene oxide was able to adhere to the surface of diatomite loaded with nano-titanium dioxide, thereby improving the dispersion of diatomite and enhancing the stability, gloss and hiding power of the ink.
[0142] In Comparative Example 3, the composite diatomaceous earth prepared by replacing the amphiphilic block copolymer with polyacrylic resin is added to the high-gloss, high-hiding ink, and its heat resistance and stability decrease, which proves that the hydrophilic chain segment of the amphiphilic block copolymer extends in the ink system, so that the composite diatomaceous earth is evenly dispersed in the ink matrix, enhancing the gloss and high hiding power of the ink, and the hydrophobic chain can also interact with the lipophilic pigment, so that the pigment has excellent dispersibility, thereby improving the stability and high hiding rate of the ink.
[0143] In Comparative Example 4, the composite diatomaceous earth prepared without adding hydroxypropyl methylcellulose was added to the high gloss, high hiding ink, and its erasability decreased, proving that hydroxypropyl methylcellulose has good film-forming properties, allowing the ink to form a continuous polymer film, so that the ink can be easily erased from the glass whiteboard.
[0144] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0145] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high gloss, high hiding ink for glass whiteboard, characterized in that: The invention comprises the following raw materials in parts by weight: 30-35 parts of pigment, 2-5 parts of composite diatomaceous earth, 8-10 parts of dispersant, 3-7 parts of resin, 0.2-0.5 parts of wetting agent, 50-60 parts of deionized water, and 5-8 parts of propylene glycol; The composite diatomaceous earth is obtained by mixing and reacting modified diatomaceous earth, an amphiphilic block copolymer and hydroxypropyl methylcellulose; The modified diatomaceous earth is obtained by mixing diatomaceous earth and n-butyl titanate, and then mixing with pretreated graphene oxide; The amphiphilic block copolymer is obtained by mixed reaction of (2-hydroxyethyl) benzyl trithiocarbonate, ε-caprolactone and acrylic acid.
2. The high gloss, high hiding ink for glass whiteboard according to claim 1, characterized in that: The composite diatomite is specifically prepared by the following steps: A1. Add n-butyl titanate and hydrofluoric acid to deionized water, stir evenly, add diatomaceous earth, stir at 500-600r / min for 30-40min, place in a reactor, react at 170-190°C for 8-10h, cool to room temperature, filter, wash, and dry to obtain diatomaceous earth loaded with nano-titanium dioxide; A2. Add graphene oxide to Tris-HCl buffer at pH 8.5, stir evenly, add dopamine, stir and react for 4-5h, filter, wash and dry to obtain polydopamine-modified graphene oxide; A3. The polydopamine-modified graphene oxide and the diatomaceous earth loaded with nano-titanium dioxide were added to deionized water, stirred at 1000-1200 r / min for 30-40 min, allowed to stand, filtered, washed, and dried to obtain modified diatomaceous earth; A4. ε-caprolactone and (2-hydroxyethyl) benzyl trithiocarbonate were added to toluene, stirred evenly, reacted at 30-40°C for 5-6h, placed in hexane to form a precipitate, collected by filtration, and dried to obtain a complex; A5. Add the complex, acrylic acid and azobisisobutyronitrile to N,N-dimethylformamide, stir evenly, react at 75-85°C for 5-6h, add chloroform, continue stirring for 10-20min, place in hexane for precipitation, collect the precipitate by filtration, wash and dry the precipitate to obtain an amphiphilic block copolymer; A6. Add the amphiphilic block copolymer and hydroxypropyl methylcellulose to deionized water, stir evenly, add modified diatomaceous earth, stir at 60-70° C. for 1-2 hours, cool to room temperature, filter, wash, and dry to obtain composite diatomaceous earth.
3. The high gloss, high hiding ink for glass whiteboard according to claim 2, characterized in that: In step A1, the ratio of n-butyl titanate, hydrofluoric acid, deionized water and diatomaceous earth is (4-6) mL: (1-1.4) mL: (45-55) mL: (10-11) g.
4. The high gloss, high hiding ink for glass whiteboard according to claim 2, characterized in that: In step A2, the ratio of graphene oxide, Tris-HCl buffer and dopamine is (2-3) g: (45-55) mL: (0.4-0.6) g.
5. The high gloss, high hiding ink for glass whiteboard according to claim 2, characterized in that: In step A3, the ratio of the polydopamine-modified graphene oxide, the diatomaceous earth loaded with nano-titanium dioxide and the deionized water is (1-2) g: (5-6) g: (25-35) mL.
6. The high gloss, high hiding ink for glass whiteboard according to claim 2, characterized in that: In step A4, the ratio of the amount of ε-caprolactone, (2-hydroxyethyl) benzyl trithiocarbonate and toluene is (1-2) g: (0.4-0.6) g: (18-22) mL.
7. The high gloss, high hiding ink for glass whiteboard according to claim 2, characterized in that: In step A5, the ratio of the amount of the complex, acrylic acid, azobisisobutyronitrile, N,N-dimethylformamide and chloroform is (1-3) g: (2-3) g: (0.03-0.07) g: (18-22) mL: (8-12) mL.
8. The high gloss, high hiding ink for glass whiteboard according to claim 2, characterized in that: In step A6, the ratio of the amphiphilic block copolymer, hydroxypropyl methylcellulose, deionized water and modified diatomaceous earth is (5-6) g: (2-3) g: (45-55) mL: (8-12) g.
9. A method for preparing a high gloss, high hiding ink for glass whiteboard according to any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: S1. The pigment, deionized water and propylene glycol were mixed, stirred at a rate of 500-600r / min for 5-10min, composite diatomaceous earth, dispersant, resin and wetting agent were added, and stirred at a rate of 1800-2000r / min for 30-40min to obtain a mixture; S2. Grind the mixture at a rotation speed of 1600-1800 rpm for 6-10 hours to obtain a high gloss, high hiding ink.
Citation Information
Cited By
Novel printing ink for decorative paper as well as preparation method and printing method of novel printing ink
CN120623836A
A new ink for decorative paper and a method for preparing and printing the same
CN120623836B
Low carbon source denitrification method
CN120698603A
Silicon nitride slurry ball milling process
CN121226027A